Telephoning in english - Naterop, B. Jean (Cambridge Univ. Press, 1997)
Telephoning in English is for professionals or trainee professionals in business, commerce and administration who need to make and answer phone calls. This fully revised and updated edition develops and consolidates practical telephone skills using activities from message-taking to spelling practice and role play.